2014
DOI: 10.1155/2014/652750
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 5 Negative Modulation in Phase I Clinical Trial: Potential Impact of Circadian Rhythm on the Neuropsychiatric Adverse Reactions—Do Hallucinations Matter?

Abstract: Metabotropic Glutamate Receptor 5 (mGluR5) negative allosteric modulators (NAMs) may play a role in some psychiatric disorders such as anxiety and depression. The pharmacokinetic profile and pharmacodynamics effects of mGluR5-NAMs have been previously reported. We performed a post hoc analysis of pharmacological and clinical data obtained from 18 young healthy female subjects who received a mGluR5-NAM in the context of a phase I drug-drug interaction study between a mGluR5 NAM and a monophasic oral contracepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…If this conclusion is correct, then modulators that specifically target mGlu 5 coupling to β-arrestin2 might avoid side effects that arise from inhibition of G q and/or mTOR pathway signaling. First-generation mGlu 5 NAMs were all identified based on inhibition of G q signaling, and in humans one adverse side effect reported following treatment with these compounds is derealization and visual hallucinations (Abou Farha et al, 2014; Pecknold et al, 1982; Porter et al, 2005). Similarly in mice, mGlu 5 NAMs exacerbate hyperlocomotion in response to treatment with the potent pyschotomimetic MK801 (Homayoun et al, 2004; Pietraszek et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If this conclusion is correct, then modulators that specifically target mGlu 5 coupling to β-arrestin2 might avoid side effects that arise from inhibition of G q and/or mTOR pathway signaling. First-generation mGlu 5 NAMs were all identified based on inhibition of G q signaling, and in humans one adverse side effect reported following treatment with these compounds is derealization and visual hallucinations (Abou Farha et al, 2014; Pecknold et al, 1982; Porter et al, 2005). Similarly in mice, mGlu 5 NAMs exacerbate hyperlocomotion in response to treatment with the potent pyschotomimetic MK801 (Homayoun et al, 2004; Pietraszek et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, for example, it has been reported that inhibition of mGlu 5 produces dose-limiting psychotomimetic effects (Abou Farha et al, 2014; Pecknold et al, 1982; Porter et al, 2005). The first-generation mGlu 5 NAMs were identified based on their ability to inhibit G q signaling mediated by phosphoinositide hydrolysis and release of Ca 2+ from intracellular stores (Cosford et al, 2003; Gasparini et al, 1999; Lindemann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additional targets within the glutamatergic system include other ionotropic receptors (AMPA, kainate) (171,172), metabotropic receptors (173), and glutamate transporters.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…CNS indications for mGlu 5 NAMs include fragile X syndrome, Ldopa induced dyskinesia in Parkinson disease, Alzheimer disease, addiction, and anxiety. Unfortunately, mGlu 5 NAMs have not been successful thus far as clinical therapeutics, in part because of the induction of side effects, including psychotomimetic activity (Pecknold et al, 1982;Porter et al, 2005;Rodriguez et al, 2005;Abou Farha et al, 2014) or the lack of efficacy in the treatment of L-DOPA-induced dyskinesia (Petrov et al, 2014) and fragile X syndrome [FRAXA mavoglurant posting (Novartis; http://www.fraxa.org/ novartis-discontinues-development-mavoglurant-afq056-fragile-x-syndrome/. in), FRAXA basimglurant posting (Roche; basimglurant, FRAXA, http://www.fraxa.org/rochereports-clinical-trial-negative-results/, in.)]…”
Section: Discussionmentioning
confidence: 99%
“…The mGlu 5 NAMs have reached or are now in active clinical studies to evaluate clinical efficacy for these disorders (Campbell et al, 2004;McGeehan et al, 2004;Pietraszek et al, 2004;Rodriguez et al, 2010;Zerbib et al, 2011). Despite these encouraging results, both clinical and preclinical studies suggest that mGlu 5 NAMs may induce ontarget adverse effects, including cognitive and memory impairments and psychotomimetic effects (Campbell et al, 2004;Porter et al, 2005;Rodriguez et al, 2010;Abou Farha et al, 2014), raising the question of whether complete blockade of mGlu 5 may contribute to these deleterious effects, thereby limiting the therapeutic utility of mGlu 5 NAMs.…”
Section: Introductionmentioning
confidence: 99%